Financial dollarization and the size of the fear - Castro, Juan Francisco (2005)
Based on the significance of a Minimum Variance Portfolio (MVP) for the understanding of dollarization equilibria, a significant strand of the debate concerned with the driving forces behind this phenomenon has focused on analyzing the determinants of the relative volatility of inflation vis-à-vis real depreciation. This analysis contributes in the identification of those factors by extending the basic CAPM formulation via the introduction of credit risk that is directly linked to the shock that determines real returns for dollar denominated assets: unanticipated shifts in the real exchange rate. We show this ingredient can end up altering the perceived relative volatility of peso and dollar assets in a way that fuels financial dollarization (by increasing the relative hedging opportunities offered by the latter). We calibrate our model using Peruvian data for the period 1998-2004, and its predictions show a better fit with observed financial dollarization ratios than those of the basic CAPM model.